Effects of High-Intensity Interval Training in Older Adults: A Systematic Review of Randomized and Non-Randomized Intervention Studies - Paula Moreira; Sérgio Ferreira; Nuno Domingos Garrido; António M. Monteiro; Pedro Afonso; Alexandra Malheiro; Joana Ribeiro; Pedro Forte (Journal of Clinical Medicine, 2026)
Background: High-intensity interval training (HIIT) is a time-efficient exercise strategy, but its effects in older adults remain incompletely established. Objective: Our objective is to synthesize evidence on the effects of HIIT and aerobic interval training (AIT) on cardiorespiratory, metabolic, functional, cognitive, psychological, and quality-of-life outcomes in older adults. Methods: This systematic review was reported in accordance with PRISMA 2020. PubMed, Scopus, and Web of Science were searched through 13 May 2026 for randomized and non-randomized longitudinal intervention studies involving participants with a mean or median age ≥ 60 years. Titles/abstracts and full texts were screened by one reviewer, with uncertain eligibility resolved through discussion with the supervisory team. Data were extracted by one reviewer and independently verified by a second reviewer. The review was retrospectively registered in INPLASY (INPLASY202660027). Results: Twenty-five eligible reports were included, representing approximately 2818 unique participants. The most consistent findings concerned cardiorespiratory fitness, with improvements in VO2peak and exercise tolerance reported across several populations. Selected functional and metabolic benefits were also observed, whereas cognitive, psychological, and quality-of-life findings were more limited and heterogeneous. HIIT produced comparable or greater improvements than moderate-intensity continuous training in some studies, but overall superiority was not established. Feasibility and adherence were generally favourable, although adverse-event reporting was inconsistent. Conclusions: HIIT/AIT may improve cardiorespiratory fitness and selected functional outcomes in older adults. However, confidence in these findings is limited by heterogeneity in populations, protocols, and outcomes, together with the predominance of risk-of-bias concerns across the included evidence. The available findings do not establish overall superiority, comparative safety, or an optimal HIIT/AIT prescription.